Operating parameter optimization and experiment of spiral outer grooved wheel seed metering device based on discrete element method - Tao Zhang; Xinglong Tang; Cong Dai; Guiying Ren (Scientific Reports)
Abstract To analyze the metering process and regulation, and to optimize the metering parameters of the spiral outer grooved wheel seed metering device, this research simulated the seed metering using EDEM software. Following the Box-Behnken testing design principle, a regression model was established to relate all factors to the performance index. The independent variables included groove rotation speed, lead angle, and groove number, while the coefficient of variation served as the response variable. The motion processes of seed-filling, seed-cleaning, and seed-protection were examined through EDEM simulations. The results indicated that groove rotation speed and lead angle significantly influenced metering performance, particularly when the lead angle ranged from 0° to 10° and the groove number was between 10 and 14. The factors affecting comprehensive performance, ranked from most to least significant, were groove rotation speed, lead angle, and groove number. However, when the lead angle was adjusted to 5° to 15° and the groove number to 12 to 16, both groove rotation speed and groove number emerged as highly significant factors affecting metering performance, with the order of influence being groove number, groove rotation speed, and lead angle. By solving the regression model for a low coefficient of variation, the optimal working parameters were determined to be a groove rotation speed of 43.15 r/min, a lead angle of 9.81°, and a groove number of 16. Verification tests revealed a coefficient of variation of 7.20%, and when compared to the simulation results, the relative error was 4.97%. This demonstrates the reliability of optimizing the parameters of the spiral outer grooved wheel seed metering device through theoretical analysis and the discrete element method.